2008
DOI: 10.1227/01.neu.0000317404.31336.69
|View full text |Cite
|
Sign up to set email alerts
|

Novel Equine Collagen-only Dural Substitute

Abstract: This study demonstrates that the new collagen-only biomatrix is a safe and effective dural substitute for routine neurosurgical procedures. The absence of local and systemic toxicity or complications and the scarce promotion of adherences and inflammation make this material appealing for its use as a dural substitute, even in cases in which the necessity of reoperation is foreseen.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(26 citation statements)
references
References 19 publications
0
25
0
1
Order By: Relevance
“…To date, many collagenbased dural substitutes have been synthesized and tested in experimental in vitro and in vivo studies, and data on the integration with nor mal tissue are available. 2,[4][5][6]8,10,12,13,[15][16][17][18][19]25,31,32 Despite the large number of these dural substitutes and the growing interest in finding "ideal" dural substi tutes that can mimic the physiological structure of human dura mater and avoid complications, there have been few studies of the microscopic morphology, disposition, and 3D architectural distribution of the collagenic component in human dura mater. 1,23,24,33 Our study aims to describe the microscopic 3D structural features and patterns of the collagen fibers as principal components of dura mater ar chitecture.…”
mentioning
confidence: 99%
“…To date, many collagenbased dural substitutes have been synthesized and tested in experimental in vitro and in vivo studies, and data on the integration with nor mal tissue are available. 2,[4][5][6]8,10,12,13,[15][16][17][18][19]25,31,32 Despite the large number of these dural substitutes and the growing interest in finding "ideal" dural substi tutes that can mimic the physiological structure of human dura mater and avoid complications, there have been few studies of the microscopic morphology, disposition, and 3D architectural distribution of the collagenic component in human dura mater. 1,23,24,33 Our study aims to describe the microscopic 3D structural features and patterns of the collagen fibers as principal components of dura mater ar chitecture.…”
mentioning
confidence: 99%
“…Було встановлено, що ушкодження м'якої та арахноїдальної оболонок забезпечує адгезію незалежно від типу замінника ТМО, що в подальшому підтвердилося [12,13]. Отже, «ідеальний замінник» ТМО має забезпечувати непроникність для рідин, відповідати фізичним властивостям ТМО людини, щоб забезпечити захист тканин мозку, бути легким і зручним для маніпуляцій під час операції при намочуванні у фізіологічному розчині; механічні властивості матеріалу мають полегшувати накладання швів і/або склеювання; мінімізувати місцеве запалення тканин для запобігання утворенню небажаного рубцювання і фіброзу або спайок; стимулювати на різних етапах наближену до фізіологічної фільтрацію клітинами (макрофагами, фібробластами) і бути матрицею для прискорення відновлення цілісності шляхом формування модифікованої ТМО; сприяти ремоделюванню судинної сітки; бути ергономічно та економічно виправданим [14,8,[15][16][17][18][19]. Обґрунтовано п'ять основних вимог до імплантату, які дають змогу наблизитися до «ідеального замінника» ТМО: по-перше, імплантат має тимчасово або постійно виконувати захисну функцію, відокремлюючи і герметизуючи субдуральний простір від епідурального; по-друге, імплантат має індукувати власні клітини до диференціювання і усунути дефіцит тканини ТМО (менінготеліальна індукція); по-третє, імплантат має сприяти інфільтрації та імплантації фібробластів (менінготеліальна провідність), що є функціональним показником тривимірної структури трансплантата; по-четверте, бажано щоб імплантат містив клітинні компоненти, здатні регенерувати нативну тканину (фібро-і менінготеліогенез); по-п'яте, імплантат має бути пластичним, тобто мати здатність легко набувати потрібної форми і відповідати хірургічному дефекту без деформації оточуючих тканин, а також відповідну еластичність (міцність до розтягнення) -здатність утримувати хірургічний шов під напруженням [20].…”
Section: теоретическое обоснование эффективности применения биополимеunclassified
“…910-polydiaxene (Ethisorb Dura Patch, DePuy Orthopaedics, Inc., Warsaw, Indiana, USA), collagen-derived substitutes, tissue glue-coated collagen sponges (TachoSil), fibrin glue, sutures with nitinol u-clips. 2,[5][6][7][8][9][10][11][12][13][14][15][16][17][18][19] Each dura substitutes have some intrinsic characteristics, and some peculiar complications have been reported. 20 In supratentorial dura openings, it has also been reported that an adaptive dural closure represents a safe and cost-effective alternative to watertight dural closure.…”
Section: Technical Reportmentioning
confidence: 99%